Learning curve and motor retention of a video game in young and older adults - Santamaría Guzmán, Keven (2015)
The purpose of the study was to compare the learning curve and motor retention of the Dance Dance Revolution (DDR) video game in healthy adults. Twenty young (M= 23.9 ± 2.8 yr.) and 18 older adults (M= 60.7 ± 5.9 yr.), were randomly assigned to two experimental conditions: a) DDR 7 trials and b) DDR 14 trials. Participants danced the same song six sessions, followed by a detraining period of eight days. Then participants returned to the laboratory and danced again in order to detect a motor retention effect. A three-way ANOVA revealed mean score interactions (sessions x groups x trials; p = 0.017). Follow-up analyses revealed differences between young and older participants in both trial sessions (p < 0.05). Compared to young adults, older adults showed a learning curve of four sessions when performing 14 trials per session. After eight days of detraining only older participants in the DDR14 condition reduced motor performance. In conclusion, older subjects can learn the DDR game after playing four sessions; however, those dancing the same song 14 times were more likely to reduce their scores after eight days of detraining. Younger participants scored high regardless of the number of trials and sessions with little variability.